Impact of Laser Power on Electrochemical Performance of CeO2/Al6061 Alloy Through Selective Laser Melting (SLM) - Fengyong Sun; Jitai Han (Crystals)
As a type of additive manufacturing technology, SLM has made significant progress in the aerospace sector because of its capacity to swiftly and effectively form metals and their composites. This work investigates the impact of laser power (260, 280, 300, 320, 340 W) on the performance of a 1.0 wt.% CeO2/Al6061 alloy prepared by SLM, including the forming quality (surface morphology and density), self-corrosion rate (SCR), and electrochemical behavior. The experimental outcomes suggest that as the laser power rises, the surface roughness exhibits an initial decline followed by an increase, whereas the density undergoes an initial increase and subsequently decreases. The SCR demonstrates a pattern of initial decrease followed by an increase as the laser power is incremented. When the laser power increases, the electrochemical activity shows the same trend. When the laser power is 280 W, the density of the sample is 98.63%, and the SCR is 2.243 × 10−4 g/cm2·min. The induced resistance of the sample caused by hydrogen evolution is small, at 7.827 × 10−20 Ω·cm2, and the polarization resistance reaches 8.048 × 10−1 Ω·cm2, suggesting superior resistance to corrosion on the part of the sample. The laser power affects the SCR and electrochemical performance of the sample by influencing its molding quality. At the laser power of 280 W, the formation quality of the sample is optimal, and the sample exhibits lower SCR and more stable electrochemical activity.